Rola organizacji pozarządowych w poprawie jakości życia osób z niepełnosprawnością wzrokową - Tikhonov, Andrey (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Human reality is constructed on the assumption that it is experienced, perceived, used, evaluated and modified by sighted people. Sensory channel which is based on the sense of sight has a significant meaning for a person. Therefore, vision impairments can jeopardize quality of life. In the whole world non-governmental organizations play an important role in Improving Quality of Life of people who have visual disability. Polish non-governmental organizations run different activities to implement the UN Convention on the Right of Persons with Disabilities. They also create conditions for independent life of blind and low-vision people
Keywords: visual disability; quality of life; non-governmental organizations